2007
DOI: 10.1074/jbc.m705258200
|View full text |Cite
|
Sign up to set email alerts
|

A Dimeric Smac/Diablo Peptide Directly Relieves Caspase-3 Inhibition by XIAP

Abstract: Caspase activation, the executing event of apoptosis, is under deliberate regulation. IAP proteins inhibit caspase activity, whereas Smac/Diablo antagonizes IAP. XIAP, a ubiquitous IAP, can inhibit both caspase-9, the initiator caspase of the mitochondrial apoptotic pathway, and the downstream effector caspases, caspase-3 and caspase-7. Smac neutralizes XIAP inhibition of caspase-9 by competing for binding of the BIR3 domain of XIAP with caspase-9, whereas how Smac liberates effector caspases from XIAP inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 48 publications
(22 reference statements)
2
78
1
1
Order By: Relevance
“…A recent study utilizing a dimeric SMAC peptide further confirmed the requirement of a two-site binding mechanism for efficient derepression of XIAP-mediated inhibition of caspase-3 and -7. 30 Interestingly, when screening the dimeric human IAP survivin, we were unable to detect any peptide hits above background (data not shown), suggesting that survivin may not possess a functional IBM groove, in line with its very weak binding of IBMs. 31 Although there are many published BIR domain affinity measurements, with K D 's in the hundreds of nanomolar to micromolar range, these are almost always carried out on peptides and not full-length natural proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study utilizing a dimeric SMAC peptide further confirmed the requirement of a two-site binding mechanism for efficient derepression of XIAP-mediated inhibition of caspase-3 and -7. 30 Interestingly, when screening the dimeric human IAP survivin, we were unable to detect any peptide hits above background (data not shown), suggesting that survivin may not possess a functional IBM groove, in line with its very weak binding of IBMs. 31 Although there are many published BIR domain affinity measurements, with K D 's in the hundreds of nanomolar to micromolar range, these are almost always carried out on peptides and not full-length natural proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of Fas and FasL could initiate transduction of the lethal apoptotic signal, thereby promoting cell apoptosis. High expression of the Fas protein could bind soluble FasL (Contassot et al, 2007), leading to the flotation of Fas-associated death domain protein (FADD), forming the death-inducing signaling complex (DISC), activating procaspase-8, causing the release of the upstream Caspase-8 (Iwase et al, 2006;WescheSoldato et al, 2007), subsequently activating Caspase-3, Caspase-6, and Caspase-7, which induces the chain reaction of the Caspase family (Yin and Ding, 2003;Gao et al, 2007), ultimately acting on structural proteins of cells, leading to cell apoptosis. Caspase-8 is a key enzyme acting in the upstream apoptosis pathway, and also acts as an important apoptosis initiation factor by activating almost all of the downstream Caspases in the apoptotic cascade (Fan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of Smac mimetics with XIAP leads to caspase activation (18,19), while the binding of Smac mimetics to cIAP proteins enhances their E3 ligase activity, thereby promoting autoubiquitination and proteasomal degradation of cIAP proteins (20)(21)(22)(23)(24). Smac mimetic-mediated depletion of cIAP proteins leads to accumulation of NIK, activation of noncanonical NF-kB signaling, and upregulation of NF-kB target genes such as TNFa.…”
Section: Targeting Iap Proteins By Smac Mimeticsmentioning
confidence: 99%